2016
DOI: 10.1016/j.jallcom.2016.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetism of Fe–Co alloy nanoparticles

Abstract: We report the hydrothermal synthesis and structure of Fe x Co 1-x alloy nanoparticles with considerable stability against oxidation under ambient atmosphere. Powder X-ray diffractometry (XRD), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), inductively coupled plasma mass spectrometry (ICP-MS), 57 FeMössbauer spectroscopy and magnetization measurements are applied to characterize the composition, morphology, crystal structure, atomic order and magnetic properties of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The STEM-EDX profiles in Figure 2e,f show that the Fe/Co ratio in the shell is similar to the core. The (Fe x Co 1-x ) 3 O 4 peaks decrease in intensity with increasing Co content, indicating a higher oxidation resistance, as already reported for nearly equimolar Fe-Co nanoalloys [28].…”
Section: Structure Morphology and Composition Of Fe-co Nanoalloyssupporting
confidence: 80%
“…The STEM-EDX profiles in Figure 2e,f show that the Fe/Co ratio in the shell is similar to the core. The (Fe x Co 1-x ) 3 O 4 peaks decrease in intensity with increasing Co content, indicating a higher oxidation resistance, as already reported for nearly equimolar Fe-Co nanoalloys [28].…”
Section: Structure Morphology and Composition Of Fe-co Nanoalloyssupporting
confidence: 80%
“…As is known, the magnetic and mechanical properties of FeCo alloys are greatly affected by their Fe/Co ratios and microstructure [22]. Our previous study has shown that high magnetization saturation (215 A·m 2 ·kg −1 ) and low coercivity (73.4 Oe) can be obtained in the chemically synthesized Fe 65 Co 35 micro-sized particles [23].…”
Section: Introductionmentioning
confidence: 99%
“…MWCNTs filled with magnetic Co-containing nanoparticles have been proved to be useful for multiple innovations in nanotechnology [1][2][3], Li/air batteries [4][5][6][7][8], magnetic-storage devices [9], magnetic composites for drug delivery [10,11], catalysts for different processes [12][13][14][15][16][17][18], as well as absorption and microwave irradiation shielding material [19][20][21][22][23][24][25][26][27][28][29][30]. It is generally accepted that the magnetic properties of nanoparticles are determined by many factors, such as chemical composition [20,[31][32][33][34][35], crystallinity [36,37], size [37][38][39][40][41] and shape [35,[42][43]...…”
Section: Introductionmentioning
confidence: 99%